Perancangan Sistem Kontrol Jarak Jauh Berbasis PID Menggunakan Blynk pada Gandrum di Kapal - Ihsanul Muqorrobin; Antonius Edy Kristiyono; Agus Prawoto (Pusat Riset dan Inovasi Nasional, 2024)
Technological developments and modern industrial needs increasingly demand high energy efficiency in refrigeration machine operations. In this context, the development of a more efficient cooling machine control system is very necessary. Good control not only helps in saving energy, but also ensures that the cooling machine operates at optimal conditions at all times. This research aims to develop a more efficient cooling machine control system using advanced sensors and the latest monitoring technology. This research was simulated using Peltier. The proposed control system adopts the Proportional-Integral-Derivative (PID) approach, which has been proven to be effective in optimizing control system performance. This PID approach has the advantage of adjusting control output quickly and precisely based on changing operational conditions. The use of the PID approach can adjust the control output quickly and accurately, which significantly improves the performance of the cooling system. IoT technology can quickly collect data and better integrate between cooling machines and monitoring systems, providing deeper insight into machine operational performance. The results of this research show that the PID system using Kp: 20 Ki: 0.8 Kd: 1.2 data can stabilize the temperature precisely and accurately compared to using other Kp, Kd, Ki data.